RANCANG BANGUN SISTEM UJIAN ONLINE BERBASIS WEB DI SMK PEMBANGUNAN KABUPATEN ROKAN HILIR-RIAU - Volvo Sihombing; Nimrot Siahaan (Politeknik Bisnis Indonesia, 2019)
SMK Pembangunan an online examination system is analyzed which is one part of the distance education system through internet technology media. Exams conducted by most educational institutions, therefore, researchers will overcome by designing a web-based online exam system design, to facilitate the community and schools, in the world of education in this case the School is still carried out conventionally. The concept of an online exam that is not related to space and time can be a solution to the constraints that exist in conventional examination methods. This system aims to make it easier for teachers to provide exams and the process of providing effective and efficient examination scores because the assessment process is given directly when students complete the exam. The study was conducted by observing the system directly so that the results of the analysis of the system needs were obtained. As a basis and reference for making an online exam system, literature study is then made to design a system database using DFD and ERD. The implementation of this online exam system is made with facilities including admin, teacher, and students which will produce output values